Interactive Multimedia-Based Learning Media in Tajwid Learning - Khoirotul Idawati; Kholidatuzzuhriyah Kholidatuzzuhriyah; Hanifuddin Hanifuddin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study aims to examine the implementation of interactive multimedia-based learning media in Tajwid learning at MTs At-Taufiq Sambongdukuh Jombang. The background of this study is based on the low ability of students to read the Qur'an according to the rules of tajwid, and the learning method is still monotonous. The study used a mixed methods approach, with data collection through observation, interviews, documentation, and pretests and posttests. The results of the study showed that the use of interactive multimedia in the form of tajwid learning videos with animation, pronunciation audio, and interactive exercises was able to increase student learning motivation, active participation, and learning outcomes. This is indicated by an increase in the average value from 64.3 to 83.7 and an N-Gain value of 0.43, which is included in the moderate category. Students also stated that this media helped them understand the material more easily. Thus, interactive multimedia learning media have proven effective in improving the quality of tajwid learning as a whole at MTs At-Taufiq